The Determinants of Central Bank Efficiency Scores: The Case of Tunisia - Ines, Abdeltif Andrea; Faiza, Bouhouch; Daly, Lamia (Business and Economic Research, 2023)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The global financial crisis of 2007 and the recent health crisis of 2019 revealed the inefficiency of the pure status of central banks. They have also prompted reflection on the question of a new "central banking". If the challenge for academic work is to redraw the theoretical contours, it is rather a question for central bankers to redefine the new framework of their action. In this sense, abundant literature has emerged examining the institutional arrangements most likely to make central banks effective. On the other hand, and to our knowledge, few analyses have focused on delineating a new intermediate status that would allow central banks to be more efficient. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">It is in this perspective of research on the efficiency of central banks that our article is written. The latter is an evaluation of the evolution of the efficiency scores of the Central Bank of Tunisia (BCT) with the change of its status, over the period from 2000 to 2020. The first part of the paper is a review of the theoretical and empirical literature on the issue of measuring central bank efficiency. In the second part, we propose to calculate and interpret the evolution of the BCT’s efficiency, with its change of status. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The calculation of the efficiency scores leads to an average score of 0.765 and also reveals frequent changes in scores and alternating periods of increase and decrease. Our economic analysis, split into two periods before and after the BCT’s independence, allows us to show that the efficiency scores recorded are not linked to its status, but rather are explained by macroeconomic, financial, monetary, and institutional variables.